(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the recent past, cloud computing technology plays major role in storage of information and big data to ensure privacy and security. The small and medium educational institutions should store their large information with high confidence and effective storage environment. The big data analysis and could computing are used to store information of small and medium educational institutions to store data dynamically and utilizing virtualized resources as a service through the Internet of Things (IoT) by selecting proper service providers (SP). In the proposed system, the selection of SP and the datacenters for small and medium educational institutions are proposed to provide privacy and security of large amount of data. The SP should provide online social network of data, information, 2D images and video of educational institutions for guarantee security of big data. The SP may have laminations in cloud space and giving space to the institutions to keep store higher size of data. The efficient and accurate data, image and video compression algorithm is proposed to minimize the data size to keep store in the cloud to occupy memory space less. The data to be stored through data centers are connected with other SP to minimize the payment cost of educational institutions. This criterion is achieved by applying Modified Genetic Algorithm (MGA) to optimize SP selection among various SP’s by achieving bandwidth allocation, maximum throughput, less error and high storage size. The experimental results show that the proposed algorithm is highly efficient and accurate for selection of SP among other providers.